A subgeneric revision of Crematogaster and discussion of regional species-groups (Hymenoptera: Formicidae) - Blaimer, Bonnie B. (Zootaxa, 2012)
Crematogaster ants are diverse, widespread and abundant in tropical, subtropical and warm-temperate climatesthroughout the world. The species diversity of this genus has been notoriously difficult to manage based upon morphologyalone, and former attempts have generated a vaguely defined subgeneric system. I propose an improvement of the previoussubgeneric classification and recognize two subgenera based upon a concurrent molecular study of the global diversity ofthese ants. Five of 13 former subgenera of Crematogaster are hereby synonymised under the subgenus OrthocremaSantschi: Neocrema Santschi syn. nov., Eucrema Santschi syn. nov., Rhachiocrema Mann syn. nov., Mesocrema Santschisyn. nov. and Apterocrema Wheeler syn. nov.. The eight remaining subgenera are synonymised under the subgenusCrematogaster sensu stricto: Decacrema Forel syn. nov., Oxygyne Forel syn. nov., Atopogyne Forel syn. nov.,Sphaerocrema Santschi syn. nov., Colobocrema Wheeler syn. nov., Paracrema Santschi syn. nov., Physocrema Forelsyn. nov. and Xiphocrema Forel syn. nov.. I present keys, morphological diagnoses and illustrations for the two revised,globally distributed subgenera Orthocrema and Crematogaster sensu stricto, based upon the worker caste. The twosubgenera can be distinguished from each other by a combination of features of the petiole, postpetiole and propodealspiracle. I also provisionally circumscribe a number of species-groups within the subgenus Crematogaster and discuss the utility of species-groups for further taxonomic, phylogenetic and ecological research on the genus Crematogaster.